(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Backyard housing cage for raising, breeding, and depasturing domesticated pigs and swine refer to any parcel of land devoted to the raising, breeding, depasturing, feeding, or watering of pigs and swine and is generally under the management of a tenant or owner. It also involves one sow and 10 heads or less and is allowed in rural areas only. The housing cage will use natural resources, such as sunlight, airflow, and wind direction, and use as little energy as possible, such as water, electricity, coal, etc. This study was conducted to determine the growth and development of various types of pigs and improve the environment within the backyard housing cage. This study used a quantitative-experimental research design to determine if the difference between the groups of respondents is significant. In terms of construction design, structural development, standard design, design accessibility, and presentation. The results of the project in terms of construction design, structural development, standard design, design accessibility, and presentation were highly acceptable as assessed by structural engineers and 4th-year Agriculture students of De La Salle Araneta University. This result indicated that the difference between the two groups of respondents in terms of the variables cited was not significant. Structural engineers obtained an overall weighted mean of 4.38, which was interpreted as very highly acceptable with the variance of 0.03, a t-computed value of 0.78, and a degree of freedom of 13 with the value of 2.650. The t-computed value was greater than the t-critical value. Therefore, the assessment of structural engineers is Accepted. Meanwhile, 4th-year Agriculture students obtained an overall weighted mean of 4.04, which was interpreted as highly acceptable with the variance of 0.03, a t-computed value of 0.78, and a degree of freedom of 13 with the value of 2.650. The t-computed value was greater than the t-critical value. Therefore, the assessment of the 4th-year Agriculture students is accepted. The respondents recommended the following; strictly arrange the room according to the feeding process, such as breeding house; keep the pig farm away from urban residential areas, schools, and hospitals; make sure that the pig house is located in the upwind direction; make sure that the fattening pig house is located in the downwind direction design terrain to a require high terrain, low groundwater level, open terrain, and good ventilation; and be consistent on some materials and design for a better appearance of the project.